Multiplex-PCR for differentiation of Mycobacterium bovis from Mycobacterium tuberculosis complex - Spositto, F.l.e. (2014)
We evaluated a multiplex-PCR to differentiate Mycobacterium bovis from M. tuberculosis Complex (MTC) by one step amplification based on simultaneous detection of pncA 169C > G change in M. bovis and the IS6110 present in MTC species. Our findings showed the proposed multiplex-PCR is a very useful tool for complementation in differentiating M. bovis from other cultured MTC species.